1980
DOI: 10.1007/bf01214860
|View full text |Cite
|
Sign up to set email alerts
|

Nonvanishing univalent functions

Abstract: The class S of functions g(z) =z+c 2 z 2 +c 3 z 3 + ... analytic and univalent in the unit disk Izr < 1 has been thoroughly studied, and its properties are well known. Our purpose is to investigate another class of functions which, by contrast, seems to have been rather neglected. This is the class S o of functions f(z)=1 + a 1 z+a 2 zZ+.., analytic, univalent, and nonvanishing in the unit disk, normalized by the condition f(0) = 1. It will become apparent that S O is closely related to the more familiar class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
163
0
2

Year Published

1984
1984
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(166 citation statements)
references
References 20 publications
1
163
0
2
Order By: Relevance
“…Hence from (2.10) we find 12) exactly as obtained in §2.2 by different means. Such results are readily extended to the case of flow driven by many sources or sinks [40], or even through slits [42].…”
Section: The Schwarz Functionsupporting
confidence: 62%
See 1 more Smart Citation
“…Hence from (2.10) we find 12) exactly as obtained in §2.2 by different means. Such results are readily extended to the case of flow driven by many sources or sinks [40], or even through slits [42].…”
Section: The Schwarz Functionsupporting
confidence: 62%
“…where K( · ) denotes the Koebe map of univalent function theory [12]. It is defined by K(ζ) = ζ/(1+ζ) 2 , and maps |ζ| < 1 onto the whole complex plane, minus the semi-infinite line segment (−∞, −1/4].…”
Section: The Momentsmentioning
confidence: 99%
“…We review some elementary facts about conformal (aka univalent) mappings, as may be found in [Dur83], for example. Let D ⊂ C be some domain.…”
Section: Conformal Mapsmentioning
confidence: 99%
“…introduces two essential geometric quantities: R 0 and a 0 , respectively, the uniquely defined (outer) conformal radius (Pólya & Szegö 1951) and the conformal centre (Pommerenke 1975;Duren 1983). The (external) conformal mapping provides a unique but not explicit definition of R 0 and a 0 , which can be interpreted as the characteristic size and location of the obstacle.…”
Section: (A) External Conformal Mappingmentioning
confidence: 99%